PENCIPTAAN ISLAMIC LEARNING COMMUNITY PADA MASYARAKAT URBAN - Marno Marno (el-hikmah, 2011)
Increasing the quality of human resources required a change in mental attitude of individuals and the creation and organization of a conducive learning environment. The process can be done with the creation of community learning. Learning community understands the concept of man as the figure of the learner (Learner), which puts the act of his life studying the totality of the scheme, not just in schools, universities and other educational institutions, but also within families and the general public. Mental construct of society is unwilling or lazy to learn to study hard or mentally as a human learner, not just by relying on internal change of their individual. Organizing the learning environment to be conducive to the establishment is a necessity that the learning environment. Learning environment that is expected to manifest both in the schools, families and communities. And through the creation of Islamic Learning Community is expected that the process of internalization of Islamic values ​​in society through the container and the behavior of religious activities in the community.